Viability assessment of magnetic resonance spectroscopy for the detection of minimal hepatic encephalopathy severity. Issue 10 (October 2015) - Meng, Ling-ping; Chen, Yuan-chang; Li, Yue-hua; Zhu, Jin-shui; Ye, Jian-lin
Highlights: The concentrations of brain metabolites were obtained by LC-model software. MRS using a 3-T MR scanner could detect cerebral metabolic changes in cirrhotic patients with MHE. Glu levels were elevated in cirrhotic patients with MHE. Glu levels could be used as a sensitive indicator to evaluate the severity of MHE in patients with cirrhosis. Abstract: Objective: To evaluate regional cerebral metabolic changes in minimal hepatic encephalopathy (MHE) patients using magnetic resonance spectroscopy (MRS) in 3T scanner. Materials and methods: This study comprised 30 cirrhotic patients with MHE, 29 cirrhotic patients without MHE and 30 healthy volunteers. Single-voxel proton MRS data in the anterior cingulate cortex (ACC) and basal ganglia were acquired using a 3-T scanner. The concentrations of N -acetylaspartate (NAA), mI (myo-inositol), glutamate (Glu), glutamine (Gln) and creatine (Cr) were obtained by LC-model software. Statistical analysis was performed to evaluate the differences between the three groups. Results: There was a significant increase in Glu for the cirrhotic patients, particularly the MHE patients. There was an elevation of Gln in the cirrhotic patients, but not in all cirrhotic patients or controls. There was a significant decrease in mI for the cirrhotic patients, but no significant difference between the two cirrhosis groups. There was no significant difference in NAA between the three groups. Conclusions: MRS using a 3-T MR scanner could detect cerebral metabolic changes in cirrhotic patients with MHE. Glu levels were elevated in cirrhotic patients with MHE; Glu levels could be used as a sensitive indicator to evaluate the severity of MHE in patients with cirrhosis.